PERANAN KONTEN TIKTOK @Vina Muliana BAGI PARA PELAKU PENCARI KERJA - Rozzy, Fachrul; Rozy, Fakhrur (Asosiasi Ide Bahasa Kepri, 2024)
The TikTok app is filled with material, and in addition to providing a platform for amusement, it also features a number of content providers that offer TikTok users helpful educational resources. Among them is Vina Muliana, an 89 million-follower content producer who gives TikTok fans a lot of helpful advice regarding the world of careers.Through in-depth interviews with a number of people who have utilized Vina Muliana's TikTok content in the field of education, this study aims to shed light on the function of TikTok content for job searchers. According to the study's findings and conclusions, Vina Muliana's professional education material has a beneficial influence on adolescents who learn what alternatives they can use to support their future careers.